2020
DOI: 10.1017/s1049023x20000357
|View full text |Cite
|
Sign up to set email alerts
|

Drug and Alcohol Related Patient Presentations to Emergency Departments during Sporting Mass-Gathering Events: An Integrative Review

Abstract: Background:Drug and alcohol consumption at sporting mass-gathering events (MGEs) has become part of the spectator culture in some countries. The direct and indirect effects of drug and alcohol intoxication at such MGEs has proven problematic to in-event health services as well as local emergency departments (EDs). With EDs already under significant strain from increasing patient presentations, resulting in access block, it is important to understand the impact of sporting and other MGEs on local health service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Moore et al suggested that team success, but not failure, may increase aggression among supporters, and not celebration, drives post-match alcohol consumption [ 18 ]. Others have reported that alcohol was a contributing factor in up to 25% of cases of ambulance transfers [ 19 ]. However, it was difficult to identify alcohol as a factor associated with traumatic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Moore et al suggested that team success, but not failure, may increase aggression among supporters, and not celebration, drives post-match alcohol consumption [ 18 ]. Others have reported that alcohol was a contributing factor in up to 25% of cases of ambulance transfers [ 19 ]. However, it was difficult to identify alcohol as a factor associated with traumatic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Mass-gathering events, social and cultural events, and sporting events are increasing in frequency. [11][12][13] The consumption of alcohol at these events heightens behaviors due to social excitement and increases the likelihood for self-harm, 14 violence, disorderly behavior, injuries, and driving under the influence. 15 As a result, this can increase the likelihood of an ARP to ED.…”
Section: Introductionmentioning
confidence: 99%
“…15 As a result, this can increase the likelihood of an ARP to ED. 16 With binge drinking attributed to 75% of all alcohol consumed, 12,17 cause for concern continues, particularly on days with a public holiday or sporting event where excessive alcohol consumption 15,18 and binge drinking behaviors are not uncommon. 17 The aim of this research was to examine the impact of ARPs to EDs on days with a public holiday or sporting event.…”
Section: Introductionmentioning
confidence: 99%
“…5 Furthermore, some people presenting to EDs with alcohol intoxication can have long stays in the ED 4 and can be violent and/or aggressive. [5][6][7][8] Alcohol, a central nervous system depressant, alters communication between the brain and body, exhibiting symptoms of poor concentration, slower reflexes, and increases the threat for risk-taking behaviour. 9 The impact from the consumption of alcohol in many countries continues to grow 5,10,11 with alcohol associated with many social and cultural events.…”
Section: Introductionmentioning
confidence: 99%